Recursive blocked algorithms for solving triangular systems?Part II two-sided and generalized Sylvester and Lyapunov matrix equations. - Jonsson, Isak; Kågström, Bo.
We continue our study of high-performance algorithms for solving triangular matrix equations. They appear naturally in different condition estimation problems for matrix equations and various eigenspace computations, and as reduced systems in standard algorithms. Building on our successful recursive approach applied to one-sided matrix equations (Part I), we now present novel recursive blocked algorithms for two-sided matrix equations, which include matrix product terms such as AXBT. Examples are the discrete-time standard and generalized Sylvester and Lyapunov equations. The means for achieving high performance is the recursive variable blocking, which has the potential of matching the memory hierarchies of today's high-performance computing systems, and level-3 computations which mainly are performed as GEMM operations. Different implementation issues are discussed, including the design of efficient new algorithms for two-sided matrix products. We present uniprocessor and SMP parallel performance results of recursive blocked algorithms and routines in the state-of-the-art SLICOT library. Although our recursive algorithms with optimized kernels for the two-sided matrix equations perform more operations, the performance improvements are remarkable, including 10-fold speedups or more, compared to standard algorithms.
Keywords: GEMM-based.; LAPACK; Matrix equations; SLICOT; SMP parallelization; Automatic blocking; Generalized Sylvester and Lyapunov; Level-3 BLAS; Recursion; Standard discrete-time Sylvester and Lyapunov; Superscalar